(untitled) (Scientia Agricola, 2007)
Eugenia brasiliensis Lam. is a variable species concerning fruit colour, with three recognized varieties. However, the definition of varieties is not easy for Myrtaceae species and not widely accepted. Two fruit colour varieties (purple and yellow) of E. brasiliensis had their essential oil composition analysed in order to give support to the existence of varieties for this species. Although, the major components in the leaf oil are the same monoterpenes for both varieties, alpha-pinene, beta-pinene and 1,8-cineol, the purple fruit variety accumulates more oxygenated sesquiterpenes (33.9%) than the one with yellow fruits (3.8%). The major differences occurred in purple fruits that present as major components caryophyllene oxide (22.2%) and alpha-cadinol (10.4%), not found in the leaf oil, and the yellow fruit oil presented a similar composition as observed for the leaves. These fruit colour varieties of E. brasilensis can be considered as two distinct chemotypes, since the sesquiterpene pathway is more operant in the purple variety than in the yellow one, in which monoterpenes are mainly accumulated.